Perverse, Anthropocentrism, and Posthumanism in Two of Edgar Allan Poe’s Stories - Wang, Quan (American & British Studies Annual, 2022)
Industrialization revolutionizes human life and engenders anthropocentrism. Edgar Allan Poe ruminates on the repercussions of anthropocentrism in his stories and speculates about a posthumanist world. “The Imp of the Perverse” challenges the prevailing standard of reason and compels us to discover the underlying world that brings current situations into existence and legitimizes perverse phenomena. The three examples of the perverse, namely, circumlocution, procrastination, and abyss obsession, outline the latent coordinates of human identity: species, time, and space. The fourth instance recapitulates the three coordinates and features underdeveloped aspects. The abrupt ending of the story (“but where?”) plunges readers into textual instability. “MS. Found in a Bottle” continues the journey of the suspended plunge: anthropocentric departure, disoriented temporality, multidimensional space. The juxtaposition of these two stories illuminates Poe’s reflections on anthropocentric hubris and posthumanist speculation.